2020
DOI: 10.1021/acs.jpcc.9b09648
|View full text |Cite
|
Sign up to set email alerts
|

Growth Model of the Tin Anodizing Process and the Capacitive Performance of Porous Tin Oxides

Abstract: Nanoporous tin oxide layers were fabricated in NaOH during potentiostatic anodization at a low potential. With increasing potential, the nanochannel became fragmentized and a stacked morphology was formed. The total anodizing current was separated into ionic current and electronic current to explain the various morphologies of nanotubes. The ionic current determines ion migration and oxide growth. The electronic current determines oxygen evolution, porous structure formation, and oxide volume expansion. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The plastic flow model originated from the description of the phenomenon that the oxides at the bottom of the tube migrates to the wall of the tube observed in the 18 O-tracer study. 9,23,84 And the model shows a PAO growth model that is completely opposite to the traditional FAD theory.…”
Section: Ionic and Electronic Current Theory And The Oxygen Bubble Mould Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The plastic flow model originated from the description of the phenomenon that the oxides at the bottom of the tube migrates to the wall of the tube observed in the 18 O-tracer study. 9,23,84 And the model shows a PAO growth model that is completely opposite to the traditional FAD theory.…”
Section: Ionic and Electronic Current Theory And The Oxygen Bubble Mould Effectmentioning
confidence: 99%
“…has been researched for quite a long time as one of hot topics, the formation mechanism of it is still not very clear. [15][16][17][18][19][20] For the lack of research on the formation mechanism, a large number of experiments should be conducted to summarized experience when developing and improving the preparation technology of nanotubes, so it is significant to clarify the formation mechanism of nanotubes in order to accurately control its morphology. After years of research and discussion, several mainstream theories have been formed in the academic community today.…”
Section: Introductionmentioning
confidence: 99%
“…At present, anodization has become a widely used technique for preparing metal oxides with various nanostructures. In addition to transition metals, some non-transition metals, like tin, have also been anodized to fabricate nanomaterials with various unique properties [203][204][205][206][207][208] . However, compared with the highly ordered AAO, the anodized films on transition metals, such as Fe, Cu and Zn, showed fewer perfect nanostructures with relatively low degrees of ordering.…”
Section: Discussionmentioning
confidence: 99%
“…Metal anodic oxide films prepared using the electrochemical anodizing method have attracted increasing attention. Significant research has been conducted on porous alumina films (PAAs) and anodic TiO 2 nanotubes (ATNTs). Anodic alumina films can be divided into dense and porous films . Dense films of anodic alumina have been widely studied because of their good dielectric properties, which can be used as dielectric films in aluminum electrolytic capacitors. However, many studies have shown that when working electrolytes contain many impurity anions (halogen anions, sulfate ions, etc.…”
Section: Introductionmentioning
confidence: 99%